Immunization of Knock-Out ?/? Interferon Receptor Mice against High Lethal Dose of Crimean-Congo Hemorrhagic Fever Virus with a Cell Culture Based Vaccine - Canakoglu, Nurettin; Berber, Engin; Tonbak, Sukru; Ertek, Mustafa; Sozdutmaz, Ibrahim; Aktas, Munir; Ozdarendeli, Aykut (Public Library Science, 2015)
Crimean-Congo hemorrhagic fever (CCHF) is an acute tick-borne zoonotic disease. The disease has been reported in many countries of Africa, Asia, the Middle East, and in Eurasia. During the past decade, new foci of CCHF have emerged in the Balkan Peninsula, southwest Russia, the Middle East, western China, India, Africa, and Turkey. CCHF virus produces severe hemorrhagic manifestations in humans with fatality rates up to 30%. Vaccine development efforts have been significantly hampered by a lack of animal models and therefore, no protective vaccine has been achieved. Lately, IFN alpha/beta receptor deficient (IFNAR(-/-)) mice have been established as a novel small animal model of CCHF virus infection. In the present study, we found that IFNAR(-/-) mice highly susceptible to CCHF virus Turkey-Kelkit06 strain. Immunization with the cell culture based vaccine elicited a significant level of protection against high dose challenge (1,000 PPFU) with a homologous CCHF virus in IFNAR(-/-) mice.
Keywords: Immune-Response; Viral Load; Pathogenesis; Infection; Epidemiology